Modification of cast alloys nanostructured material - P. A. Vitiaz; N. A. Svidunovich; D. V. Kuis; Yu. A. Nikalaichyk; S. L. Rovin (Литьë и металлургия)
The third article of the series devoted to the application of nanomaterials and nanotechnologies in industry in general and, first of all, in metallurgy, materials science and foundry is presented. This article deals with the use of nanomaterials for the improvement of ferrous and non-ferrous alloys by micro-alloying and modifying methods, as well as the synthesis of new composite materials. The results of research on C-B-Fe composites obtained at the Belarusian State Technological University, a method for modifying gray cast iron with micro-additives of abrasive slurries of high-speed steels, proposed by specialists of BNTU and OJSC «MTW», and aluminum alloys modified with nanostructured carbideand nitride-containing powders developed by Belarusian, Bulgarian and Russian scientists are presented.